2019
DOI: 10.1108/md-11-2018-1211
|View full text |Cite
|
Sign up to set email alerts
|

Inter-project knowledge transfer in project-based organizations: an organizational context perspective

Abstract: Purpose Numerous studies highlight the importance of knowledge transfer between projects, but the influence factors are still debated. As a contribution to the identified gap, the purpose of this paper is to investigate the role of organizational context, project characteristics and social relations in the inter-project knowledge transfer within the project-based organizations (PBOs). Design/methodology/approach This paper collects the data through 268 sample questionnaires from Chinese construction sectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 68 publications
3
35
0
Order By: Relevance
“…Existing research also explored the factors affecting knowledge transfer from the perspective of the relationship between the transfer subjects. Relevant factors include trust (Minbaeva, 2007), similarity (Ren et al , 2020), geographical distance (Ren et al. , 2018) and so forth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research also explored the factors affecting knowledge transfer from the perspective of the relationship between the transfer subjects. Relevant factors include trust (Minbaeva, 2007), similarity (Ren et al , 2020), geographical distance (Ren et al. , 2018) and so forth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research also explored the factors affecting knowledge transfer from the perspective of the relationship between the transfer subjects. Relevant factors include trust (Minbaeva, 2007), similarity (Ren et al, 2020), geographical distance (Ren et al, 2018) and so forth. Sun et al (2019) proposed that among the elements of the relationship dimension, trust is the most important factor, because it is the basis of any interpersonal relationship or interorganizational relationship.…”
Section: Literature Review 21 Knowledge Transfer Factors In Organizat...mentioning
confidence: 99%
“…X. Ren et al [13] showed that the organizational context (meeting system, reward system and shared culture) and project characteristics (similarity and urgency) are previously affecting social relations (communication, trust and reciprocity) between project teams, and their social relations further influence the effectiveness of interproject knowledge transfer. The influencing factors were widely represented in J.T.…”
Section: Related Workmentioning
confidence: 99%
“…Its essence consists in self-reproduction of knowledge (Zhang, Li, Aziz-alaoui, Bertelle, Guan, Zou, 2016, p. 2). Compared to transfer, the process is closely related to the social context (Vlajcic, Marzi, Caputo, Dabic, 2019, p. 196)it requires mutual interaction between its participants (Ren, Yan, Wang, He, 2019), it is conditioned by the characteristics of knowledge in the form of its viscosity and ambiguity (Klarl, 2014, p. 2), more strongly associated with silent knowledge and strongly dependent on the organisational culture of the enterprise (Paliszkiewicz, Svanadze, Jikia, 2017, p. 37). Therefore, knowledge diffusion takes into account the positive effects of its transfer, along with its conditions and context.…”
Section: Importance Of Knowledge Transfer and Diversity Of Contemporamentioning
confidence: 99%
“…Among others, from this point of view, the role of knowledge transfer increases even more (Secundo, Toma, Schiuma, Passiante, 2019), especially that it is both recognised as basic and necessary to succeed in the field of its management in organisations (Gou, Li, Lyu, Lyu, 2019) and gains particular importance in the context of diversity of employees and the circumstances of their work (Ren, Yan, Wang, He, 2019). A need arises to propose solutions concerning the shaping of optimal conditions for its implementation, both universal ones and some dedicated to specific groups of stakeholders.…”
Section: Introductionmentioning
confidence: 99%